The complete chloroplast genome of Madhuca hainanensis (Sapotaceae), an endemic and endangered timber species in Hainan Island, China. Issue 3 (4th March 2021) - Wang, Yong; Wang, Hai-Tao; Chen, Yu-Kai; Yu, Jing; Yang, Yong
Abstract: Madhuca hainanensis Chun & F.C.How is an endangered and endemic species in Hainan Island, and it was ranked as a VU (Vulnerable) species in China. In this study, we reported its complete chloroplast (cp) genome sequence based on high throughput sequencing data. The complete cp genome was 159, 630 bp in length, containing two short inverted repeat (IRs) of 26, 093 bp, a large single copy (LSC) region of 88, 846 bp and a small single copy (SSC) region of 18, 598 bp. Totally, the cp genome contained 131 genes, including 86 protein coding genes (PCG), eight rRNA genes and 37 tRNAs. The GC contents of this genome was 36.8%. A maximum likelihood (ML) phylogenetic analysis indicates that M. hainanensis is closely related to Sinosideroxylon wightianum .